TEST EQUIPMENT SERIAL COMMUNICATION INTERFACE RS-232 DB-9 TYPE CONNECTORS ON TESTING TECHNIQUES INSITU - Derry Ekasaputra; Drs. Lingga Hermanto, MMSI (Jurnal Sistem Komputer, 2005)
At this writing will be made prober interface RS-232 in situ testing (testing onlocation) when the system interfaces operate without causing disturbances operatingsystem itself. For that tool is designed so that the information will be observed in thetest can be easily accessed via the display in the form of light and the values of thesignal information in the form of voltage level. To avoid the imposition of thiscommunication interface, the tool is equipped with the buffer. It is expected that thistool can provide rapid information, communication failures in the process of datathrough computer communication port.